Sistem Pendukung Keputusan Pemilihan Karyawan Baru di Communion Coffee Brewer Metode SMART - Asmara Andhini; Muh Abdul Aziz Nasuha; Ika Ayu Pertiwi; Ahmad Wahyudi (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
Employee recruitment is a critical aspect of human resource management that significantly influences the success and sustainability of a company. Communion Coffee Brewer, a company in the food and beverage industry, faces challenges in effectively recruiting employees to ensure alignment with company needs and culture. To address this, the implementation of Decision Support System (DSS) using the SMART Methodology proves to be a relevant solution. This method allows for objective evaluation based on predefined criteria while streamlining the decision-making process. By integrating this technology, Communion Coffee Brewer can enhance efficiency and effectiveness in recruitment, support sustainable company growth, and strengthen its long-term operations.